Career Planning in Vocational High School - Dery Septa Yanni; Khairani Khairani (Universitas Negeri Padang, 2021)
This research is motivated by the phenomenon of students who do not understand their interests and talents so that they have an impact on their careers and do not get information from counseling teachers regarding career information. Career planning is a provision or process that an individual must undergo and go through in an effort to achieve the desired career goals. This study aims to describe the career planning of vocational students which includes, 1) self-knowledge and understanding, 2) knowledge and understanding of work and 3) integration of personal information with existing jobs. This type of research is a quantitative descriptive study. The sample of this research was 246 students of class X and XI SMKN 1 Pasaman in the academic year 2020/2021 who were selected using the simple random sampling technique. The research instrument used a questionnaire about the career planning of students of SMKN 1 Pasaman with the Likert scale model answer choices. Data analysis using descriptive statistical analysis techniques. The results revealed that:, 1) the career planning of SMKN 1 Pasaman students from all aspects was generally in the good category with a percentage of 58.13%, 2) the career planning of SMKN 1 Pasaman students from the aspect of knowledge and understanding of themselves was generally in the good category with a percentage 52.44%, 3) career planning of SMKN 1 Pasaman students from the aspect of knowledge and understanding of work is generally in a good category with a percentage of 47.97% and 4) career planning for SMKN 1 Pasaman students from the aspect of integrating self-information with existing jobs, generally in pretty good category with a percentage of 55.28%.